Addressing the issue of under-utilization of precursor material in SILAR process: Simultaneous preparation of CdS in two different forms – Thin film and powder. (July 2018) - Ravichandran, K.; Porkodi, S.
Abstract: To overcome the major limitation of the successive ionic layer adsorption and reaction (SILAR) technique – the under-utilization of the precursor material – in the present work, simultaneous fabrication of CdS thin films and CdS powder is attempted. CdS films were prepared by employing SILAR technique using cadmium acetate dihydrate and thiourea as cationic and anionic precursor materials for Cd and S, respectively. The precipitated powder materials in the cationic and anionic baths which are usually discarded as wastage are collected and processed to obtain CdS powders. In another trial, the cationic and anionic bath solutions are mixed and the resultant precipitate is collected for characterization. The obtained CdS in thin film and powder forms are analyzed for structural, surface morphological, optical, compositional and photocatalytic properties. The results clearly showed that the obtained CdS films are good candidates for considering them for solar cell applications. Similarly, CdS powders obtained from the mixture of cationic and anionic bath solutions are found to have good photocatalytic efficacy. Thus the demerits of under-utilization of precursor materials in SILAR process for the deposition of CdS films is overcome to certain extent as 63% of the wastage is recovered as useful product.